La distopía cotidiana - Gallardo-Saborido, Emilio J. (Verba hispanica, 2024)
In Latin America, modernity can be read in the tension between utopian and dystopian discourses. This paper begins with a brief overview of some of the works that in this sense marked or mark the 20th and 21st centuries in Latin America. From there, it focuses on the novel Tongolele no sabía bailar (2021) by the Nicaraguan writer Sergio Ramírez, placing it within the Latin American dystopian tradition and framing it within the neo-crime literature produced in Spanish since the final decades of the 20th century. The novel is the third part of a trilogy headed by police inspector/private investigator Dolores Morales, and portrays the demonstrations that shook Nicaragua in 2018, denouncing their repression by the government of Daniel Ortega and Rosario Murillo. The central theme of tyranny is analyzed with a focus on how violence and paranoia serve to sustain hegemonic political power. To do this, conceptual tools from political anthropology are used, particularly the findings of F. G. Bailey in Stratagems and Spoils (1969). Finally, it concludes by confirming the capacity of the ruling regime to remain in power.
Keywords: 21 st.; dictator novel; diktatorski roman; distopija; dystopia; neo-crime fiction; neokriminalni roman; Nicaraguan literature; nikaragovska književnost; Ramírez, Sergio